Normal Glucose Metabolism in Carnivores Overlaps with Diabetes Pathology in Non-Carnivores - Schermerhorn, Thomas (Frontiers in Endocrinology, 2013)
Carnivores, such as the dolphin and the domestic cat, have numerous adaptations that befit consumption of diets with high protein and fat content, with little carbohydrate content. Consequently, nutrient metabolism in carnivorous species differs substantially from that of non-carnivores. Important metabolic pathways known to differ between carnivores and non-carnivores are implicated in the development of diabetes and insulin resistance in non-carnivores: 1.) the hepatic glucokinase (GCK) pathway is absent in healthy carnivores yet GCK deficiency may result in diabetes in rodents and humans, 2.) healthy dolphins and cats are prone to periods of fasting hyperglycemia and exhibit insulin resistance, both of which are risk factors for diabetes in non-carnivores. Similarly, carnivores develop naturally-occurring diseases such as hemachromatosis, fatty liver, obesity and diabetes that have strong parallels with the same disorders in humans. Understanding how evolution, environment, diet and domestication may play a role with nutrient metabolism in the dolphin and cat may also be relevant to human diabetes.